2018
DOI: 10.1080/14712598.2018.1513486
|View full text |Cite
|
Sign up to set email alerts
|

Stargardt macular dystrophy and evolving therapies

Abstract: Stargardt macular dystrophy (STGD1) is a hereditary retinal degeneration that lacks effective treatment options. Gene therapy, stem cell therapy, and pharmacotherapy with visual cycle modulators (VCMs) and complement inhibitors are discussed as potential treatments. Areas covered: Investigational therapies for STGD1 aim to reduce toxic bisretinoids and lipofuscin in the retina and retinal pigment epithelium (RPE). These agents include C20-D3-vitamin A (ALK-001), isotretinoin, VM200, emixustat, and A1120. Avaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 71 publications
2
61
0
Order By: Relevance
“…Our data demonstrates that fenretinide also impairs photopic vision, thus, concerns arise over potential adverse drug reactions in the clinic with fenretinide use to treat diseases such as geographic atrophy, cancer, acne, cystic fibrosis and psoriasis. Likewise, emixustat is now in Phase III clinical trial for the inherited retinal degeneration Stargardt disease with the intention of suppressing retinoid cycling (37). We show that the photopic visual cycle overcomes emixustat which may have significant impact on clinical outcomes.…”
Section: Differential Requirements Of Rpe65 For Immediate and Early Cmentioning
confidence: 86%
See 1 more Smart Citation
“…Our data demonstrates that fenretinide also impairs photopic vision, thus, concerns arise over potential adverse drug reactions in the clinic with fenretinide use to treat diseases such as geographic atrophy, cancer, acne, cystic fibrosis and psoriasis. Likewise, emixustat is now in Phase III clinical trial for the inherited retinal degeneration Stargardt disease with the intention of suppressing retinoid cycling (37). We show that the photopic visual cycle overcomes emixustat which may have significant impact on clinical outcomes.…”
Section: Differential Requirements Of Rpe65 For Immediate and Early Cmentioning
confidence: 86%
“…To investigate the effects of visual cycle inhibitors on cone vision, we assayed the effects of pharmacological agents, previously used in human clinical trials (36,37), on the vision of 5 dpf zebrafish larvae. Previous studies demonstrate 5 dpf zebrafish rely exclusively on cones for vision (38).…”
Section: Fenretinide But Not Emixustat Impairs Late Cone Photopic Vmentioning
confidence: 99%
“…STGD1 (MIM# 248200) is an autosomal recessive disease caused by mutations in the gene encoding the ATP binding cassette type A4 ( ABCA4 ; MIM# 601691; Allikmets et al, ). With an estimated prevalence of 1 in 10,000 individuals (Blacharski et al, 1988), STGD1 is the most frequent juvenile inherited macular dystrophy and ABCA4 is the most frequently mutated IRD‐associated gene (Hussain et al, ; Tanna, Strauss, Fujinami, & Michaelides, ). In an inventory of all reported variants and cases, 5,962 (allelic) variants identified in 3,928 cases were listed (Cornelis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrates that fenretinide also impairs photopic vision, thus, concerns arise over potential adverse drug reactions in the clinic with fenretinide use to treat diseases such as geographic atrophy, cancer, acne, cystic fibrosis and psoriasis. Likewise, emixustat is now in Phase III clinical trial for the inherited retinal degeneration Stargardt disease with the intention of suppressing retinoid cycling (37). We have shown that the photopic visual cycle overcomes emixustat which may have significant impact on clinical outcomes.…”
Section: Differential Requirements Of Rpe65 For Immediate and Early Cmentioning
confidence: 93%